Management of Patients on Antithrombotic Agents Undergoing Endoscopy - Joon Sung Kim (The Korean Journal of Gastroenterology, 2018)
Antithrombotic agents are used increasingly in Asia. The management of patients on antithrombotics undergoing elective or emergency endoscopy has become an increasing clinical challenge for gastroenterologists. Current practice guidelines have been developed by societies from western countries. On the other hand, these guidelines cannot meet the specific needs of the Asian Pacific region, raising the need for separate guidelines in Asia. This review compares the recommendations of previous guidelines with the most recently published Asian guidelines regarding the management of patients on antithrombotic agents undergoing elective and emergency endoscopy.